Trading for the future: signaling in permit markets - Bård Harstad; Gunnar S. Eskeland (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
Tradable permits are celebrated as a political instrument since they allow (i) firms to equalize marginal abatement costs through trade and (ii) the government to distribute the burden of the policy in a politically fair and feasible way. These two concerns, however, conflict in a dynamic setting. Anticipating that high-cost firms will receive more permits in the future, firms purchase excessive amounts of permits to signal high costs. This raises the price above marginal costs and distorts abatements. In fact, it is better with non-tradable permits if the heterogeneity between the firms is small, if the (shadow) price for permits is large, and if the government redistributes permits frequently.
Keywords: 330; Tradable permits; private information; signaling